2003
DOI: 10.1016/s1364-6613(03)00192-x
|View full text |Cite
|
Sign up to set email alerts
|

Iconic and non-iconic stages in number development: the role of language

Abstract: Is language the key to number? This article argues that the human language faculty provides the cognitive equipment that enables humans to develop a systematic number concept.Crucially, this concept is based on non-iconic representations that involve relations be tween relations: relations between numbers are linked with relations between objects. In contrast to this, language-independent numerosity concepts provide only iconic representations. The pattern of forming relations between relations lies at the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 49 publications
2
48
0
5
Order By: Relevance
“…Recently the value of including language as measure has been stressed in the prediction of numeracy development (Heim, Amunts, Drai, Eickhoff, Hautvast, & Grodzinksy, 2012;Purpura et al, 2011;Romano, Babchishin, Pagani, & Kohen, 2010;Sarnecka et al, 2007;Wiese, 2003). Oral language skills include receptive language, expressive language and the understanding of grammatical rules and the structure of language (Purpura et.…”
Section: Language In Kindergarten and Early Arithmeticmentioning
confidence: 99%
“…Recently the value of including language as measure has been stressed in the prediction of numeracy development (Heim, Amunts, Drai, Eickhoff, Hautvast, & Grodzinksy, 2012;Purpura et al, 2011;Romano, Babchishin, Pagani, & Kohen, 2010;Sarnecka et al, 2007;Wiese, 2003). Oral language skills include receptive language, expressive language and the understanding of grammatical rules and the structure of language (Purpura et.…”
Section: Language In Kindergarten and Early Arithmeticmentioning
confidence: 99%
“…Human processing of numbers has intrigued researchers from various disciplines such as anthropology (Urton and Brezine, 2005), linguistics (Gordon, 2004;Pica et al, 2004;Wiese, 2003), psychology (Gallistel and Gelman, 1992;Gelman and Butterworth, 2005;Moyer and Landauer, 1967), and cognitive neuroscience (Brannon, 2006;Dehaene et al, 2003;Fias et al, 2003;Nieder, 2005). Previous reviews focused on the question whether the same representation exists for different notations of numbers (i.e., the issue of abstract numerical representation; Brannon, 2006;Dehaene et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental and cross-cultural studies have indeed shown that children use their fingers early in life while learning basic arithmetic operations and the conventional sequence of counting words (Butterworth, 1999b). More particular, fingers have been found to contribute to (a) giving an iconic representation of numbers (Fayol & Seron, 2005), (b) keeping track of the number words uttered while counting up or down at the numerable chain level (Fuson et al, 1982), (c) prompting the understanding that every symbolic number is a sum and/or a multiple of 10 (the base 10 numerical system) and that 10 is equal to 2 Â 5 (the sub-base 5 system), (d) sustaining the induction of the one-to-one correspondence principle (Graham, 1999) by helping children to coordinate the act of tagging the object with saying the number word (Alibali & DiRusso, 1999;Fuson, 1988), and (e) sustaining the assimilation of the stable-order principle by supporting the emergence of a routine to link fingers to objects in a sequential culture-specific stable order (Wiese, 2003a(Wiese, , 2003b.…”
mentioning
confidence: 99%
“…Interestingly, these abilities are assumed to rest in the parietal cortex, a brain area that is often associated with the dorsal visual pathway. Furthermore, because finger-counting and finger-montring habits are culturally determined (e.g., European children start counting with a closed fist and unbend one finger after the other, whereas Chinese children start counting with an open hand and bend one finger after the other [Butterworth, 1999b;Ifrah, 1981;Wiese, 2003a;Wiese, 2003b]), the question arises as to whether vision is critical or not for the elaboration of these interactions. The study of congenitally blind children represents a unique opportunity to investigate this issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation